EDUKASI KEBERSIHAN LINGKUNGAN SEBAGAI UPAYA PENCEGAHAN STUNTING PADA KADER DI WILAYAH PUSKESMAS PULO BRAYAN - Sitio, Sri Sudewi Pratiwi; Amirah, Nada; Tanjung, Lina Febriani; Putri, Rizqi Nanda; Damanik, Yunita Syahputri; Sembiring, Efrata (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Stunting is a condition where a child's growth and development do not match their age due to a prolonged lack of adequate nutrition. Children who experience growth delays from early on until the age of 5 will notice this. difficult to fix, so it will continue into adulthood. Dirty environmental factors and slum settlements are significant causes of stunting. Cleanliness is a step towards implementing a clean and healthy lifestyle by not defecating inappropriately, washing hands with soap, managing drinking water and food, and handling household waste through safe and proper domestic wastewater management. The purpose of the community service activities involving lecturers and students from the public health and hospital administration study programs. The field of Administration Science consists of: 1.) enhancing students' skills as a strategic goal to increase community participation through environmental cleanliness education; 2.) student involvement in boosting community participation in preventing stunting in the Pulo Brayan sub-district through environmental hygiene education; 3.) providing an overview of the understanding of stunting, its causes, the standards for defining stunting conditions, followed by environmental hygiene education focused on toilet cleanliness. The method used in this activity is environmental hygiene education through lectures and direct socialization between households. The result of this activity is the education provided to the cadres about the relationship between environmental cleanliness and the occurrence of stunting, as the community does not have toilets, leading to waste disposal in rivers or nearby places of worship. Holding lectures and Q&A sessions as part of community service is considered to enhance knowledge and provide new perspectives to the cadres. The community service activities in Pulo Brayan Kota District, Medan Barat District, Medan City, were carried out as planned through collaboration with various parties such as the Pulo Brayan village head, the Pulo Brayan health center, PSKM and ARS DHDT students, the Pulo Brayan community, and the PKK mothers in Pulo Brayan District. Keywords: Stunting, Environmental Cleanliness, Latrines